PROFESSIONAL LEARNING COMMUNITIES AS A LEADERSHIP STRATEGY IN THE 21ST CENTURY SCHOOL MANAGEMENT - Chediak, Sheylla; Kunnari, Irma; Inforsato, Edson do Carmo [UNESP]; Amorim Junior, Jorge W. de (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This paper aims to present a theoretical discussion about the concept of Professional Learning Community ( PLC) and to relate it to the proposal of a school management model, focused on the teacher professional development aligned with the demands of the 21st Century. This paper also represents a case study which analyses the school management regarding the maintenance of a PLC in two schools in Finland. This initial study points to the need of carrying out an applied research in schools in Brazil so that implementation and its assessment can be done, beginning with a hypothesis that a PLC meets the demands for a school management model that can empower teachers, promote staff well-being, provide lifelong learning opportunities and consequently improve the quality of students' learning.
Keywords: Professional Learning Community; Teacher professional development; School management